Sistem Pendukung Keputusan Kelayakan Sertifikasi Pada Tenaga Tukang Terampil Dengan Metode Saw Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kab. Tanjung Jabung Timur - Andika, Inno Reza; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2022)
Decision support system is a system used to support decision making in an organization, company, or educational institution to direct, train, assess and evaluate students and training. Builders as skilled construction workers through the Indonesian Construction Workers Certification Acceleration Program. Work ownership certification is an obligation for construction workers as stipulated in Law No. 2 of 2017 concerning Construction Services. The role of artisans as part of the construction workforce in infrastructure development in Indonesia is very important. Plumbers in the field also determine the quality of buildings. The certification is the standardization of workforce competence, be it an expert, intermediate or skilled craftsman. The purpose of this study is to determine the eligibility of a qualified craftsman certified by the method (Simple Additive Weighting) or also known as the weighted sum method and requires the process of normalization of the decision matrix (X) to a scale that can be compared with all existing alternative ratings. With the criteria set by the government through the public works department and local spatial planning, which cooperates with the construction services development agency, which ends with the granting of certificates to the craftsman who has been declared to have passed the certification test.